HUBUNGAN FAKTOR KESEHATAN LINGKUNGAN RUMAH DENGAN RESIKO KEJADIAN DEMAM BERDARAH DBD DI WILAYAH PUSKESMAS LINGKAR BARAT KOTA BENGKULU - Rahman, Habibur; Martono, Agus; Simarmata, Marulak; Brata, Bieng; Barchia, M.Faiz (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Dengue Hemorrhagic Fever (DHF) is an environment-based disease (physical, biological and sausage) that is widely found in tropical and sub-tropical regions whose transmission is through mosquito bites of Aedes aegypti and Aedes albopictus species. Efforts to prevent the transmission of this disease by breaking the mosquito breeding chain itself are by carrying out 3M activities (Draining, Closing, Burying) plus and suppressing other transmission factors so that it is closely related to behavior. The purpose of this study was to determine the relationship between dengue incidence to knowledge, the condition of the Water Reservoir (TPA) and the presence of Aedes sp mosquito larvae in the West Ring Health Center area of Bengkulu City. This research is a quantitativeresearch with a type of analytical research. The results showed that the three variables had a significant relationship with the presence of Aedes sp larvae, namely the level of knowledge with a p value of 0.044, the condition of water reservoirs with a p value of 0.03 and the presence of mosquito larvae with a p value of 0.035. While the most influential / most dominant factor is knowledge, followed by the existence of larvae and water reservoirs, with Odd Ratio values (1.399; 0.623; and 0.535). Keywords: Dengue fevver, factors, home environmental health